Analysis of Students’ Errors in Solving Problems in Class XII IPA SMA Negeri 5 Soppeng - Winaldi; Gusniwati; Andi Aras (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2020)
This study aims to describe the types of student errors and the factors that cause errors in class XII MIPA 1 SMA Negeri 5 Soppeng in solving math problems on statistics. This research is qualitative research using a descriptive research methodology approach. Data collection was carried out using written tests and interviews. The subjects in this study were 31 students of class XII MIPA 1 SMA Negeri 5 Soppeng taken by purposive sampling. The types of student error were classified according to the Newman procedure. The results of this study indicate that in solving mathematical problems, the research subjects make types of errors; reading errors, comprehension errors, transformation errors, process skills errors, and encoding errors. The factors that cause student errors are poor network connection in looking for references to work on questions, unfamiliarity with online learning, lack of understanding of statistics submitted online, difficulty in the calculation part, lack of ability or not being used to writing things that are known and things those who are asked in the questions correctly, lack of practice working on practice questions related to statistics, do not like maths lessons, are in a hurry to work on the completion process. The solution to avoid or minimize the occurrence of these errors is to look for appropriate learning methods, look for references via the internet or from YouTube videos, students are actively practicing working on problem-solving types, practicing answering.